Students’ Mathematics Creative Thinking Skills Reviewed by Habits of Mind on Probing-Prompting Learning with Open-Ended Approach - Arifah, Nazihatun; Asikin, Mohammad; Dwijanto, Dwijanto (Universitas Negeri Semarang, 2021)
This research aims to describe mathematics creative thinking skill reviewed by habits of mind on probing-prompting learning with open-ended approach. The used research method is mixed method with concurrent embedded design. The population of this research consisted of X grade SMA N 1 Sumpiuh, in academic year 2019/2020. The subjects consisted of seven selected students based on high, moderate, and low habits of mind. The technique of collecting the data used mathematics creative thinking skill test, habits of mind questionnaire, and interview. The results showed that the description of students' mathematics creative thinking skills in each category of high, moderate, and low habits of mind had different mastery of mathematics creative thinking skills. This difference does not depend on the category of students' habits of mind, but because of students’ learning activities.